Evaluation of Single Common Powertrain Lubricant (SCPL) Candidates for Fuel Consumption Benefits in Military Equipment - Warden, Robert; Hansen, Gregory; Comfort, Allen (2011)
The Single Common Powertrain Lubricant (SCPL) program is seeking to develop an all-season (arctic to desert), fuel-efficient, multi-functional powertrain fluid with extended drain capabilities. To evaluate candidate lubricants for the purpose of fuel consumption effects, a test cycle was developed using the GEP 6.5L(T) engine found in the HMMWV. Field data collected at Ft. Hood, TX was used to determine a set of speed, load and temperature points which could be reproduced consistently in test-cell operation. These points were condensed into a 14-mode cycle for use within the SCPL program. In addition to fresh condition oil, some lubricants were evaluated at end-of-life drain conditions to determine consumption effects over time. Results from the program indicated a significant fuel consumption benefit with lower viscosity lubricants when compared to current in-use military engine oils. Presented at the NDIA Ground Vehicle Systems Engineering and Technology Symposium held in Dearborn, MI on 9-11 August 2011. Published in the Proceedings of the NDIA Ground Vehicle Systems Engineering and Technology Symposium, August 2011. Prepared in collaboration with U.S. Army TARDEC Fuels and Lubricants Research Facility, Southwest Research Institute, San Antonio, TX.